Rabhia - de Almeida, Fernanda Pinto (Kronos, 2024)
Lucílio Manjate, Rabhia (Maputo: Alcance, 2019), 139 pp., ISBN: 9789928794338 The growing interest in Mozambican crime fiction since the early 2000's reflects a move to portray underexplored characters, stories and spaces of postcolonial life through the lens of the police procedural. This period has not only seen numerous debates in Mozambique surrounding the purported 'death' of Mozambican literature, but it has coincided with a significant literary shift towards the crime novel. Works such as Mia Couto's Under the Frangipani and Lília Momplé's Neighbours have drawn Anglophone readers and scholars into these conversations.1 Since then, Mozambican writers have continued to expand the boundaries of the crime novel in order to question the status of 'engaged' literature and to offer readers nuanced explorations of the genre alongside that of the country's social inheritances of colonialism, liberation struggle, civil war and ongoing armed conflict.